2021
DOI: 10.1136/ijgc-2021-002753
|View full text |Cite
|
Sign up to set email alerts
|

Uterine serous carcinoma: key advances and novel treatment approaches

Abstract: The incidence and mortality rates from endometrial cancer continue to increase worldwide, while rates in most other cancers have either plateaued or declined considerably. Uterine serous carcinoma represents a fraction of all endometrial malignancies each year, yet this histology is responsible for nearly 40% of all endometrial cancer-related deaths. These deaths disproportionately affect black women, who have higher rates of advanced disease at diagnosis. Molecular genetic analyses reveal major alterations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 66 publications
0
36
0
3
Order By: Relevance
“…This patient also had TP53 and PIK3CA mutations with a low mutation frequency and microsatellite stable. These results are not unusual for this patient population but do have implications on prognosis and treatment [ 28 ]. In one study it was found that individuals with both TP53 and PIK3CA mutations had worse survival prognoses than those with only TP53 mutation [ 29 ].…”
Section: Discussionmentioning
confidence: 96%
“…This patient also had TP53 and PIK3CA mutations with a low mutation frequency and microsatellite stable. These results are not unusual for this patient population but do have implications on prognosis and treatment [ 28 ]. In one study it was found that individuals with both TP53 and PIK3CA mutations had worse survival prognoses than those with only TP53 mutation [ 29 ].…”
Section: Discussionmentioning
confidence: 96%
“…However, a recent phase-II trial for the study of pembrolizumab in combination with lenvatinib (a multi-kinase inhibitor) has shown a 50% response rate in women with advanced serous endometrial disease. 64 The progression-free survival (7.2 vs 3.8 months; HR 0.56) and the overall survival (OS: 18.3 vs 11.4 months; HR 0.62) were significantly improved with the combination of both versus pembrolizumab monotherapy. 65 Based on this study, pembrolizumab with lenvatinib was also approved in an accelerated manner by the FDA for patients with previously treated metastatic EC whose tumors were not MSI-H/dMMR.…”
Section: Endometrial Cancermentioning
confidence: 93%
“…Previously, hysteroscope-guided peritumoral injection of ICG administered to >200 patients from a single center showed a para-aortic SLN detection rate of >50% [49]. However, a multicenter prospective randomized study of 165 patients who were administered hysteroscopeguided injection alone versus those administered cervical injection reported better pelvic SLN identification and a higher bilateral detection rate with the cervical injection method [50]. Another alternative is the fundal injection of ICG using a laparoscopic approach, which is usually performed sequentially with cervical ICG injection and pelvic SLN sampling.…”
Section: Methods Of Fine-tuning Sln Mapping With Respect To Paraaorti...mentioning
confidence: 99%